Therapeutic-intensive approaches in the neonatal triad in small animals: A literature review (Research, Society and Development, 2024)
The neonatal phase of dogs and cats is critical due to the immaturity of the organic systems, making neonates susceptible to the neonatal triad (hypothermia, hypoglycemia, and dehydration). Understanding physiology allows for the early detection of complications that can be fatal if not promptly treated. Objective: To describe the therapeutic management of the neonatal triad and updates, given its high mortality rate. Methodology: A narrative review was conducted using the databases Google Scholar and Scielo, utilizing keywords such as "neonatal triad," "hypothermia," "hypoglycemia," and "dehydration" in veterinary neonatology. Articles published between 2000 and 2023 were included, covering clinical trials, observational studies, and specialized books in small animal medical practice. Results: Effective practices include maintaining body temperature with warmed fluids (35-37ºC) and incubators (29.4-35ºC and humidity 50-65%). Hydration should be administered at doses of 4 mL/100 g for dogs and 2-3 mL/100 g for cats, either in boluses every 30 minutes or through continuous infusion (0.5 mL/100 g/h). The correction of hypoglycemia involves bolus administration of 25% glucose (1 mL/100 g), followed by continuous infusion with 2.5-5% glucose. Conclusion: Early management of temperature, glycemia, and dehydration, including immune safety, nutrition, and guidance for caregivers, is essential to reduce mortality and improve the health of neonates.